Akap1 Deficiency Promotes Mitochondrial Aberrations and Exacerbates Cardiac Injury Following Permanent Coronary Ligation via Enhanced Mitophagy and Apoptosis. - Gabriele Giacomo Schiattarella (PLoS ONE, 2016)
A-kinase anchoring proteins (AKAPs) transmit signals cues from seven-transmembrane receptors to specific sub-cellular locations. Mitochondrial AKAPs encoded by the Akap1 gene have been shown to modulate mitochondrial function and reactive oxygen species (ROS) production in the heart. Under conditions of hypoxia, mitochondrial AKAP121 undergoes proteolytic degradation mediated, at least in part, by the E3 ubiquitin ligase Seven In-Absentia Homolog 2 (Siah2). In the present study we hypothesized that Akap1 might be crucial to preserve mitochondrial function and structure, and cardiac responses to myocardial ischemia. To test this, eight-week-old Akap1 knockout mice (Akap1-/-), Siah2 knockout mice (Siah2-/-) or their wild-type (wt) littermates underwent myocardial infarction (MI) by permanent left coronary artery ligation. Age and gender matched mice of either genotype underwent a left thoracotomy without coronary ligation and were used as controls (sham). Twenty-four hours after coronary ligation, Akap1-/- mice displayed larger infarct size compared to Siah2-/- or wt mice. One week after MI, cardiac function and survival were also significantly reduced in Akap1-/- mice, while cardiac fibrosis was significantly increased. Akap1 deletion was associated with remarkable mitochondrial structural abnormalities at electron microscopy, increased ROS production and reduced mitochondrial function after MI. These alterations were associated with enhanced cardiac mitophagy and apoptosis. Autophagy inhibition by 3-methyladenine significantly reduced apoptosis and ameliorated cardiac dysfunction following MI in Akap1-/- mice. These results demonstrate that Akap1 deficiency promotes cardiac mitochondrial aberrations and mitophagy, enhancing infarct size, pathological cardiac remodeling and mortality under ischemic conditions. Thus, mitochondrial AKAPs might represent important players in the development of post-ischemic cardiac remodeling and novel therapeutic targets.